2014
DOI: 10.1111/avsc.12122
|View full text |Cite
|
Sign up to set email alerts
|

Mapping continuous forest type variation by means of correlating remotely sensed metrics to canopy N:P ratio in a boreal mixedwood forest

Abstract: Abbreviations IS = imaging spectroscopy; LiDAR = light detection and ranging; N:P ratio = nitrogen to phosphorus ratio; N = nitrogen; P = phosphorus Nomenclature Little (1979) Abstract Questions: Can the ratio of nitrogen to phosphorus (N:P ratio) be predicted at canopy level using imaging spectroscopy (IS) and light detection and ranging (LiDAR) remote sensing data? How do temporal variation and difference in spatial resolution of these data sources affect prediction accuracy of the canopy N:P ratio?Location:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 69 publications
(108 reference statements)
0
9
0
Order By: Relevance
“…Spatial distribution of canopy macronutrient concentration at GRFS mimics the functional type variation and thus, the spatial patterns of macronutrients are driven by the functional types' distribution at the site. Forest type variation was also found to be the underlying factor in explaining the observed spatial patterns of canopy N:P ratio at this site [54].…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Spatial distribution of canopy macronutrient concentration at GRFS mimics the functional type variation and thus, the spatial patterns of macronutrients are driven by the functional types' distribution at the site. Forest type variation was also found to be the underlying factor in explaining the observed spatial patterns of canopy N:P ratio at this site [54].…”
Section: Discussionmentioning
confidence: 70%
“…Crown closure reflects the amount of green foliage in the canopy and directly controls the spectral response collected over the canopy. Crown closure was identified as the biophysical variable linking spectral data to canopy N:P ratio over two seasons at the same site [54] and it was also found to be controlling the spectral response in jack pine stands of northern Ontario, Canada [69].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, Townsend et al [52] disagreed that the %N-NIR relationship is necessarily spurious, as Wright et al [14] and Ollinger [53] indicated that the canopy structure and leaf properties may co-vary across plant functional types. Species and plant functional types (i.e., broadleaf and coniferous forest types) account for most of the variance of canopy chemistry that has been demonstrated across tropical [54][55][56][57], temperate [58], boreal forests [29,59], and Mediterranean ecosystems [60]. The link between species and canopy biochemistry can be explained by the concept of 'global leaf economics spectrum' [14], which means that the key plant traits such as leaf mass per area, specific leaf area, leaf nitrogen, leaf phosphorous, leaf lifespan, and photosynthesis fall into a spectrum across plant species, and species converge towards the functional traits globally [14,61].…”
Section: Introductionmentioning
confidence: 99%